Project Work – a Challenge for Learner and Teacher - Drelinga, Elga; Jonāne, Lolita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
A topical issue in current sustainable education debate is seeking ways to support inquisitiveness, thinking skills and freedom of choice among learners as well as awaken their responsibility to pursue systematic and independent learning. Projects of various kinds are a plausible means for reaching such educational aims. Project work is essentially focused on achieving a specific result. It welcomes diversity, encourages meaningful learning and promotes comprehension of interconnections. This study explores project work in terms of the philosophical underpinnings of the teaching and learning process, investigates the opportunities of using project work in lower elementary school, appraises teachers’ positive experience and considers relevant solutions for pre-service teacher training and in-service professional development. The study suggests that strategic planning of teaching and learning, teaching and learning through cooperation, and evaluation of learning achievements are most fundamental aspects of project work. The study concludes by emphasising the key importance of creative interaction among the teacher, the learner and the society.